The Conversion of Iberia’s Bells - Katz, Dana E. (Material religion, 2021)
In 997 the bells of Santiago de Compostela converted to Islam. Al-Mansur, de facto ruler of al-Andalus, destroyed the Christian shrine of Santiago de Compostela and carried off its bells to Cordoba. He then transformed the bells into lamps, hanging them in the Great Mosque. This conversion story (and the bells’ subsequent return to Santiago in 1236) reverberates in the historical record through its numerous retellings in Arabic, Latin, and Spanish sources. In this article, I explore conversion as a topos to study what inanimate objects reveal about the animate world. The bells are not extant, yet the record-keeping properties of Iberian chronicles make accessible the bells’ storied past. Here I explore the material trace left by the bells in Christian and Muslim cultures. I cull diverse Iberian chronicles to investigate how Santiago de Compostela and the Great Mosque of Cordoba are bound together through the bells’ metal alloy.